Extracutaneous glomus tumour of the trachea - Brzeziński, Daniel; Łochowski, Mariusz Piotr; Jesionek-Kupnicka, Dorota; Kozak, Józef (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
A 38-year-old man presenting expiratory stridor and high-grade dyspnoea was admitted to hospital in Lodz in February 2013. Chest radiographs and computed tomography scans showed a solid lesion in the upper part of the trachea occluding 85% of the airway lumen. A segmental resection of the trachea with a subsequent end-to-end anastomosis was performed. Histopathology showed an extracutaneous glomus tumour. There were no postoperative complications. Tracheal resection is the primary curative method in cases of this rare tumour.